Hydrogen Bonding and Interaction between Diethylene Glycol and Water: Density, Excess Molar Volume and Spectral Studies - Huo, Tianrui; Zhang, Jianbin; Li, Chunping; Li, Qiang; Liu, Zhanying; Zhang, Tong (Asian Journal of Chemistry, 2010)
Density was determined over the whole concentration range for diethylene glycol (DEG) + water (DEGW) in the range of 298.15-323.15 K. The density (r) values was used to calculate the excess molar volume (Vm E), which was used to discuss hydrogen bonding and interaction of DEG with water. The computed results are fitted to a Redlich-Kister equation to obtain the coefficients and estimate the standard deviations between the experimental and calculated quantities. These results suggest that the likely complex of 1 DEG molecule bonding with 2 water molecules is formed at maximal excess molar volume, which displayed lower absorption capabilities for SO2 (122 mg L-1) when the concentration of SO2 arrived at F1 = 5 × 10-4 in the gas phase. When conventional spectroscopic techniques were used for inspection of spectral changes of various DEGWs, the results suggest that DEG can interact with water by hydrogen bonding and interaction.